Mediasi Kepercayaan Konsumen Pada Hubungan Kualitas Produk Dan Persepsi Risiko Terhadap Keputusan Pembelian Di Marketplace (Survey pada Mahasiswa Universitas Sultan Ageng Tirtayasa) - Simarmata, Mervyn Yudikaputra; Taufik, Edi Rahmat; Damarwulan, Liza Mumtazah (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2021)
The number of e-commerce businesses provides fierce competition in the marketplace in Indonesia. This study aims to analyze the role of trust as a mediator between the relationship of product quality and risk perception of purchasing decisions in the marketplace. The study used a survey method, which was carried out on Sultan Ageng Tirtayasa University students with accidental sampling technique. The amount of data processed as many as 100 samples by the SEM-PLS method. Based on the research results obtained that all hypotheses are accepted, meaning that product quality has a positive and significant effect on purchasing decisions and trust, risk perception has a negative and significant effect on purchasing decisions and trust, trust has a positive and significant effect on purchasing decisions. Trust is proven capable of mediating the relationship between product quality and risk perception of purchasing decisions.